(untitled) (Medico Legal Update, 2021)
“Whiplash Injury” describes those injury deriving from the sharp whipping movement of both head and neck, produced at the moment of a traffic accident, particularly following collision from behind, head-on or side collisions. The use of safety belts has led to a reduction in deaths deriving from front-end collisions, but also to an increase in cases of typical whiplash. There are two types of forces that cause whiplash injuries in rear-end car crashes: external forces applied to the body by the seat and head restraint, and internal forces generated by the activation of body’s muscles. The combination of these forces causes differential motion of the cervical spine, which results in neck tissues’ strain. This event can affect all neck structures: facet joints capsule, muscles, intervertebral disks, nerves and vessels. We report a case of a 68-year-old woman. The subject, while driving her car, hit head-on a car moving in the opposite direction and died immediately. At autopsy the major findings were limited to multiple rib fractures and fracture of the fifth cervical vertebra with epidural hematoma. This case demonstrates that, even in the absence of direct traumatism, a potentially lethal epidural hematoma may occur as a result of whiplash.